Cut Costs Plant Your Own Vegetables - Sunday Star, Rashvinjeet S.Bedia (2008)
WHENEVER Dr Rokiah Talib 64 visits her sister in their hometown of Ipoh she brings back plants and vegetables And this tickles her sister.